Molybdenum disulfide-based adsorbing material and preparation method thereof
By preparing CeO2/MoS2 composite nanomaterials and modifying them, the problem of insufficient adsorption, selectivity and stability of existing adsorbent materials in wearable artificial kidneys is solved, and efficient and stable adsorption performance and reduced cytotoxicity are achieved. effect.
Patent Information
- Application Number
- CN202411439766.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-15
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption material preparation, and in particular relates to an adsorption material based on molybdenum disulfide and a preparation method thereof. Background Art
[0002] Molybdenum disulfide is a nanomaterial with a special layered structure. Due to its unique physical and chemical properties, it has shown wide application potential in many fields. In the field of artificial kidney technology, the adsorption performance of molybdenum disulfide has attracted particular attention, mainly due to its large specific surface area and abundant active sites on the edge.
[0003] In the application of artificial kidneys, molybdenum disulfide can be used as an efficient adsorption material to remove toxins and waste from the blood. At the same time, by adjusting the synthesis conditions of molybdenum disulfide, such as the molar ratio of reactants, reaction time and temperature, its morphology and structure can be optimized to improve its adsorption performance. In the design of artificial kidneys, wearable dialysis machines and bioartificial kidneys are two main research directions. Wearable dialysis machines need to solve the problem of dialysate regeneration, and molybdenum disulfide plays an important role in it, which helps to improve adsorption efficiency and selectivity. In addition, the photoelectric properties and catalytic degradation properties of molybdenum disulfide may also play a role in the biosensors and photocatalytic systems of artificial kidneys. However, the application of molybdenum disulfide in artificial kidney technology still faces challenges, including how to improve its adsorption performance and enhance stability.
[0004] Chinese patent CN 115554975 B discloses an adsorbent material and its preparation method and application. The adsorbent material is a flower-shaped molybdenum disulfide composite material modified by cerium dioxide, which is prepared by hydrothermal method and can be used as an efficient adsorbent for uremic toxins. Compared with activated carbon and MoS2, the present invention solves the technical problem that the adsorption, selectivity and stability of the adsorbent material in the dialysis fluid purification device of the wearable artificial kidney in the prior art still need to be further improved, and has efficient adsorption performance; however, the adsorbent material may be cytotoxic and is not conducive to long-term use.
[0005] Therefore, it is urgent to develop an adsorption material based on molybdenum disulfide with good adsorption performance. Summary of the invention
[0006] In view of the existing technical problems, the purpose of the present invention is to provide an adsorption material based on molybdenum disulfide and a preparation method thereof. The adsorption material of the present invention has high adsorption, high selectivity and high stability, and thus has a good market prospect.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] In one aspect, the present invention provides a method for preparing an adsorption material based on molybdenum disulfide, comprising the following steps:
[0009] S1. Mix ammonium molybdate tetrahydrate and thiourea and perform a hydrothermal reaction to prepare nano-molybdenum disulfide;
[0010] S2. The nano-molybdenum disulfide obtained in step S1, cerium nitrate hexahydrate, and deionized water are mixed, ultrasonically dispersed for 5-10 minutes, hydrochloric acid is added, heated to 90-100°C, stirred for 10-25 minutes, cooled, washed, and dried to obtain a CeO2 / MoS2 composite nanomaterial;
[0011] S3. The CeO2 / MoS2 composite nanomaterial obtained in step S2 and 1-2 mg / mL of the modified solution were mixed, heated and ultrasonicated, and then deionized water was added, centrifuged once, the precipitate was washed, and then dispersed with deionized water, centrifuged twice, the upper liquid was taken, and dried to obtain a modified CeO2 / MoS2 composite nanomaterial;
[0012] S4. Disperse the modified CeO2 / MoS2 composite nanomaterial obtained in step S3 in deionized water, add a surfactant, ultrasonically disperse, add the modified graphene, ultrasonically disperse, then add a reducing agent, perform a hydrothermal reaction, wash, and dry to obtain an adsorption material.
[0013] The reaction mechanism and effects of the present invention are as follows:
[0014] 1. The present invention uses ammonium molybdate and thiourea as reactants and uses a hydrothermal method to prepare nano molybdenum disulfide. During the generation process of nano molybdenum disulfide, excess thiourea will be adsorbed on the surface of the initially generated MoS2 nanometers, hindering the growth of crystals and generating more active sites on the surface of nano MoS2. Furthermore, the applicant combines nano molybdenum disulfide and cerium nitrate hexahydrate by ultrasound to form a CeO2 / MoS2 composite nanomaterial; then, a modified liquid (6-amino-1-mercaptohexane hydrochloride aqueous solution) of a thiol substance is modified on the active sites, which is more conducive to its functional modification and improves biocompatibility. Furthermore, the present invention uses graphene and chloroacetic acid as reactants to prepare modified graphene under alkaline conditions. Not only can the graphene itself be modified to the surface of the CeO2 / MoS2 composite nanomaterial through an amidation reaction, but the cationic surfactant will generate charge attraction with the negative charge on the surface of the modified graphene, so that the graphene and the CeO2 / MoS2 composite nanomaterial are better combined, the stability is improved, and finally a graphene / CeO2 / MoS2 composite adsorption material is prepared.
[0015] The adsorbent material of the present invention has no obvious agglomeration phenomenon after being left to stand for a long time in different temperature environments, and has good stability. In addition, the present invention increases the total specific surface area and adsorption sites by modifying molybdenum disulfide, thereby improving the adsorption rate and adsorption capacity of the adsorbent material for uremic toxins.
[0016] In some embodiments, the specific steps of step S1 are as follows:
[0017] Add ammonium molybdate tetrahydrate, thiourea and deionized water into a reactor, perform ultrasonic treatment at 100-200W for 20-45min, heat to 180-210°C, react for 16-24h, cool, centrifuge once, take the precipitate, wash it with deionized water 3-4 times, disperse it with deionized water, centrifuge it twice, take the upper liquid, and dry it to obtain nano molybdenum disulfide.
[0018] In some embodiments, the mass ratio of ammonium molybdate tetrahydrate to thiourea in step S1 is 1:(2-2.2).
[0019] In some embodiments, the mass ratio of nano-molybdenum disulfide and cerium nitrate hexahydrate in step S2 is (2.4-3):1.
[0020] In some embodiments, the modifying liquid in step S3 is an aqueous solution of 6-amino-1-mercaptohexane hydrochloride.
[0021] In some embodiments, the usage ratio of the CeO2 / MoS2 composite nanomaterial and the modified liquid in step S3 is 1g: (600-800)ml.
[0022] In some embodiments, the parameters of the first centrifugation in step S3 are 10000-15000 rpm for 20-40 min, and the parameters of the second centrifugation are 3500-6000 rpm for 10-20 min.
[0023] In some embodiments, the conditions of the heating ultrasound in step S3 are: heating temperature 30-40°C, ultrasound power 100-200W.
[0024] In some embodiments, the mass ratio of the modified CeO2 / MoS2 composite nanomaterial and the modified graphene in step S4 is (45-55):1.
[0025] In some embodiments, the surfactant in step S4 is a cationic surfactant.
[0026] Preferably, the cationic surfactant is any one or more of dodecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, and didodecyldimethylammonium bromide.
[0027] In some embodiments, the method for preparing the modified graphene in step S4 comprises the following steps:
[0028] The graphene oxide and deionized water are mixed, ultrasonically dispersed, and then chloroacetic acid and sodium hydroxide are added, ultrasonicated, stirred for 10-16 hours, centrifuged, washed, dried, and ground to obtain modified graphene.
[0029] In some embodiments, the mass ratio of graphene oxide, chloroacetic acid, and sodium hydroxide is 1:(2.2-2.6):(3-3.8).
[0030] Another aspect of the present invention provides an adsorption material based on molybdenum disulfide obtained by the preparation method.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The adsorption material of the present invention has high adsorption, high selectivity and high stability, and thus has good market prospects.
[0033] 2. The present invention increases the total specific surface area and adsorption sites by modifying molybdenum disulfide, thereby improving the adsorption performance of the adsorption material for uremic toxins.
[0034] 3. The modified graphene of the present invention can not only modify itself to the surface of CeO2 / MoS2 composite nanomaterials through amidation reaction, but also the cationic surfactant will generate charge attraction with the negative charge on the surface of the modified graphene, so that the graphene and CeO2 / MoS2 composite nanomaterials are better combined, the stability is improved, and then the adsorption performance is improved. DETAILED DESCRIPTION
[0035] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, rather than to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0036] Various adsorption materials were prepared according to the ratios of various raw materials and the preparation methods specified in the following examples and comparative examples.
[0037] In order to facilitate those skilled in the art to implement the present invention, some raw material manufacturers of the embodiments and comparative examples are described as follows:
[0038] There is no special restriction on the raw materials used, and all of them can be purchased from the market.
[0039] Preparation Example 1
[0040] The preparation method of modified graphene A comprises the following steps:
[0041] 1 g of graphene oxide and 100 ml of deionized water were mixed, and ultrasonic dispersion was performed at 100 W for 30 min. Then, 2.4 g of chloroacetic acid and 3.6 g of sodium hydroxide were added, and ultrasonic dispersion was performed at 200 W for 45 min. The mixture was stirred for 16 h, centrifuged, washed with deionized water until neutral, freeze-dried at -30 ° C for 12 h, and ground to obtain modified graphene A.
[0042] Preparation Example 2
[0043] The preparation method of modified graphene B is the same as that of Preparation Example 1, except that the amount of chloroacetic acid added is 2.2 g.
[0044] Preparation Example 3
[0045] The preparation method of modified graphene C is the same as that of Preparation Example 1, except that the amount of sodium hydroxide added is 2.8 g.
[0046] Example 1
[0047] A method for preparing an adsorption material based on molybdenum disulfide comprises the following steps:
[0048] S1. 1.5 g of ammonium molybdate tetrahydrate, 3.15 g of thiourea and 50 ml of deionized water were added to the reactor, ultrasonicated at 150 W for 35 min, heated to 200 ° C, reacted for 20 h, cooled to room temperature, centrifuged at 12000 rpm for 30 min, the precipitate was washed with deionized water 4 times, dispersed with deionized water, centrifuged at 4500 rpm for 15 min, the upper layer was taken, and dried at 60 ° C for 48 h to obtain nano molybdenum disulfide;
[0049] S2. 1 g of nano-molybdenum disulfide obtained in step S1, 0.37 g of cerium nitrate hexahydrate, and 200 ml of deionized water were mixed, ultrasonically dispersed for 8 min, 5 ml of 0.12 mol / L hydrochloric acid was added, heated to 95 ° C, stirred for 15 min, cooled to room temperature, washed 3 times with anhydrous ethanol, then washed 3 times with deionized water, and dried at 60 ° C for 16 h to obtain CeO2 / MoS2 composite nanomaterials;
[0050] S3. 1 g CeO2 / MoS2 composite nanomaterial obtained in step S2 and 700 ml 1.5 mg / mL 6-amino-1-mercaptohexane hydrochloride aqueous solution were mixed, heated to 35 ° C, 150 W ultrasonic for 20 min, and then 500 ml of deionized water was added, centrifuged at 12000 rpm for 30 min, the precipitate was washed 4 times with deionized water, and then dispersed with 300 ml of deionized water, centrifuged at 4500 rpm for 15 min, the upper layer was taken, and dried at 60 ° C for 24 h to obtain a modified CeO2 / MoS2 composite nanomaterial;
[0051] S4. Disperse 0.5 g of the modified CeO2 / MoS2 composite nanomaterial obtained in step S3 in 100 ml of deionized water, add 50 mg of dodecyltrimethylammonium bromide, ultrasonically disperse at 200 W for 20 min, add 10 mg of modified graphene A, ultrasonically disperse at 500 W for 40 min, then add 0.2 g of thiourea, heat to 180°C, stir to react for 6 hours, cool to room temperature, wash 4 times with deionized water, dry to constant weight at a vacuum degree of 1.0 Pa and a temperature of -40°C to obtain an adsorbent material.
[0052] Example 2
[0053] A method for preparing an adsorption material based on molybdenum disulfide comprises the following steps:
[0054] S1. 1.5 g of ammonium molybdate tetrahydrate, 3 g of thiourea, and 50 ml of deionized water were added to a reactor, ultrasonicated at 200 W for 20 min, heated to 210 ° C, reacted for 16 h, cooled to room temperature, centrifuged at 10000 rpm for 40 min, the precipitate was washed 4 times with deionized water, dispersed with deionized water, centrifuged at 3500 rpm for 20 min, the upper layer was taken, and dried at 60 ° C for 24 h to obtain nano molybdenum disulfide;
[0055] S2. 1 g of nano-molybdenum disulfide obtained in step S1, 0.33 g of cerium nitrate hexahydrate, and 200 ml of deionized water were mixed, ultrasonically dispersed for 5 min, 5 ml of 0.12 mol / L hydrochloric acid was added, heated to 90 ° C, stirred for 25 min, cooled to room temperature, washed 3 times with anhydrous ethanol, then washed 3 times with deionized water, and dried at 60 ° C for 16 h to obtain CeO2 / MoS2 composite nanomaterials;
[0056] S3. Mix 1 g of CeO2 / MoS2 composite nanomaterial obtained in step S2 and 600 ml of 2 mg / mL 6-amino-1-mercaptohexane hydrochloride aqueous solution, heat to 30 ° C, ultrasonicate at 100W for 20 min, add 500 ml of deionized water, centrifuge at 10000 rpm for 40 min, wash the precipitate with deionized water 4 times, disperse it with 300 ml of deionized water, centrifuge at 3500 rpm for 20 min, take the upper layer, and dry it at 60 ° C for 24 h to obtain a modified CeO2 / MoS2 composite nanomaterial;
[0057] S4. Disperse 0.45 g of the modified CeO2 / MoS2 composite nanomaterial obtained in step S3 in 100 ml of deionized water, add 50 mg of dodecyltrimethylammonium bromide, ultrasonically disperse at 200 W for 20 min, add 10 mg of modified graphene A, ultrasonically disperse at 500 W for 40 min, then add 0.2 g of thiourea, heat to 180°C, stir to react for 6 hours, cool to room temperature, wash 4 times with deionized water, and dry to constant weight at a vacuum degree of 1.0 Pa and a temperature of -40°C to obtain an adsorbent material.
[0058] Example 3
[0059] A method for preparing an adsorption material based on molybdenum disulfide comprises the following steps:
[0060] S1. 1.5 g of ammonium molybdate tetrahydrate, 3.3 g of thiourea, and 50 ml of deionized water were added to a reactor, ultrasonicated at 100 W for 45 min, heated to 180 ° C, reacted for 24 h, cooled to room temperature, centrifuged at 15000 rpm for 20 min, the precipitate was washed 4 times with deionized water, dispersed with deionized water, centrifuged at 6000 rpm for 10 min, the upper layer was taken, and dried at 60 ° C for 24 h to obtain nano molybdenum disulfide;
[0061] S2. 1 g of nano-molybdenum disulfide obtained in step S1, 0.41 g of cerium nitrate hexahydrate, and 200 ml of deionized water were mixed, ultrasonically dispersed for 10 min, 5 ml of 0.12 mol / L hydrochloric acid was added, heated to 100 ° C, stirred for 10 min, cooled to room temperature, washed 3 times with anhydrous ethanol, then washed 3 times with deionized water, and dried at 60 ° C for 16 h to obtain CeO2 / MoS2 composite nanomaterials;
[0062] S3. 1 g CeO2 / MoS2 composite nanomaterial obtained in step S2 and 700 ml 1.5 mg / mL 6-amino-1-mercaptohexane hydrochloride aqueous solution were mixed, heated to 35 ° C, 150W ultrasound for 20 min, and then 500 ml of deionized water was added, centrifuged at 15000 rpm for 20 min, the precipitate was washed 4 times with deionized water, and then dispersed with 300 ml of deionized water, centrifuged at 6000 rpm for 10 min, the upper layer was taken, and dried at 60 ° C for 24 h to obtain a modified CeO2 / MoS2 composite nanomaterial;
[0063] S4. Disperse 0.55 g of the modified CeO2 / MoS2 composite nanomaterial obtained in step S3 in 100 ml of deionized water, add 50 mg of dodecyltrimethylammonium bromide, ultrasonically disperse at 200 W for 20 min, add 10 mg of modified graphene A, ultrasonically disperse at 500 W for 40 min, then add 0.2 g of thiourea, heat to 180 ° C, stir to react for 6 hours, cool to room temperature, wash 4 times with deionized water, and dry to constant weight at a vacuum degree of 1.0 Pa and a temperature of -40 ° C to obtain an adsorbent material.
[0064] Example 4
[0065] A method for preparing an adsorption material based on molybdenum disulfide is the same as that in Example 1, except that an equal amount of modified graphene B is used to replace modified graphene A.
[0066] Example 5
[0067] A method for preparing an adsorption material based on molybdenum disulfide is the same as that in Example 1, except that an equal amount of modified graphene C is used to replace modified graphene A.
[0068] Example 6
[0069] A method for preparing an adsorbent material based on molybdenum disulfide is the same as that in Example 1, except that the amount of 6-amino-1-mercaptohexane hydrochloride aqueous solution added in step S3 is 570 ml.
[0070] Example 7
[0071] A method for preparing an adsorption material based on molybdenum disulfide is the same as that in Example 1, except that the amount of modified graphene A added in step S4 is 8.6 mg.
[0072] Example 8
[0073] A method for preparing an adsorption material based on molybdenum disulfide is the same as that in Example 1, except that the amount of thiourea added in step S1 is 2.7 g.
[0074] Example 9
[0075] A method for preparing an adsorption material based on molybdenum disulfide is the same as that in Example 1, except that the amount of cerium nitrate hexahydrate added in step S2 is 0.46 g.
[0076] Comparative Example 1
[0077] A method for preparing an adsorption material based on molybdenum disulfide is the same as that in Example 1, except that an equal amount of commercially available graphene oxide is used to replace the modified graphene A.
[0078] Comparative Example 2
[0079] A method for preparing an adsorption material based on molybdenum disulfide comprises the following steps:
[0080] S1. 1.5 g of ammonium molybdate tetrahydrate, 3.3 g of thiourea, and 50 ml of deionized water were added to a reactor, ultrasonicated at 100 W for 45 min, heated to 180 ° C, reacted for 24 h, cooled to room temperature, centrifuged at 15000 rpm for 20 min, the precipitate was washed 4 times with deionized water, dispersed with deionized water, centrifuged at 6000 rpm for 10 min, the upper layer was taken, and dried at 60 ° C for 24 h to obtain nano molybdenum disulfide;
[0081] S2. Mix 1 g of nano-molybdenum disulfide obtained in step S1, 0.41 g of cerium nitrate hexahydrate, and 200 ml of deionized water, and ultrasonically disperse for 10 min. Add 5 ml of 0.12 mol / L hydrochloric acid, heat to 100 ° C, stir and react for 10 min, cool to room temperature, wash 3 times with anhydrous ethanol, and then wash 3 times with deionized water, and dry at 60 ° C for 16 h to obtain CeO2 / MoS2 composite nanomaterials, which are adsorption materials.
[0082] Effect evaluation:
[0083] The adsorption materials prepared in the above-mentioned Examples 1-9 and Comparative Examples 1-2 were tested and analyzed, and the specific results are shown in Table 1.
[0084] Performance Test:
[0085] Urea adsorption performance measurement: Take 0.1g of adsorption material to adsorb 20ml of urea solution (the mass concentration of urea solution is 300mg / L), and measure the urea concentration in the solution after 2h at 37℃.
[0086] Determination of creatinine adsorption performance: Take 0.1g of adsorption material to adsorb 50ml of creatinine solution (the mass concentration of creatinine solution is 200mg / L), and measure the creatinine concentration in the solution after 2h at 37℃.
[0087] Table 1
[0088] Serial number Urea adsorption capacity (mg / g) Creatinine adsorption capacity (mg / g) Example 1 82.2 88.7 Example 2 80.3 87.9 Example 3 81.8 89.0 Example 4 73.1 78.4 Example 5 75.9 79.7 Example 6 72.7 77.2 Example 7 70.5 75.6 Example 8 72.9 76.5 Example 9 74.2 79.6 Comparative Example 1 62.6 69.5 Comparative Example 2 52.1 59.2
[0089] From the results in Table 1, it can be seen that the urea adsorption capacity and creatinine adsorption capacity of the adsorption materials prepared in Examples 1-3 are relatively high.
[0090] Examples 4-5 and Comparative Example 1 Compared with Example 1, when preparing modified graphene, Examples 4-5 changed the mass ratio of graphene oxide, chloroacetic acid and sodium hydroxide, making it difficult for the modified graphene to effectively combine on the surface of the modified CeO2 / MoS2 composite nanomaterial, thereby deteriorating the stability of the adsorption material; Comparative Example 1 uses an equal amount of commercially available graphene oxide to replace modified graphene A, and graphene oxide is difficult to effectively combine with the modified CeO2 / MoS2 composite nanomaterial, both of which will reduce the adsorption capacity of the adsorption material.
[0091] Compared with Example 1, when preparing the modified adsorption material, Example 6-9 changes the dosage ratio of CeO2 / MoS2 composite nanomaterial and 1-2 mg / mL modification liquid, and the grafted amino groups are reduced; Example 7 changes the mass ratio of modified CeO2 / MoS2 composite nanomaterial and modified graphene, reducing the combination effect of the two; Example 8 changes the mass ratio of ammonium molybdate tetrahydrate and thiourea, causing partial crystal growth and a reduction in active sites; Example 9 changes the mass ratio of nano molybdenum disulfide and cerium nitrate hexahydrate, reducing surface active sites and resulting in poor synergistic effect, thereby reducing the adsorption capacity of the adsorption material.
[0092] Compared with Example 1, Comparative Example 2 only combines CeO2 and MoS2 without introducing graphene, which greatly reduces the adsorption capacity of the adsorption material.
[0093] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.
Claims
1. A method for preparing an adsorbent material based on molybdenum disulfide, characterized in that: The following steps are included: S1. Mix ammonium molybdate tetrahydrate and thiourea and perform a hydrothermal reaction to prepare nano-molybdenum disulfide; S2. The nano-molybdenum disulfide obtained in step S1, cerium nitrate hexahydrate, and deionized water are mixed, ultrasonically dispersed for 5-10 minutes, hydrochloric acid is added, heated to 90-100°C, stirred for 10-25 minutes, cooled, washed, and dried to obtain a CeO2 / MoS2 composite nanomaterial; S3. The CeO2 / MoS2 composite nanomaterial obtained in step S2 and 1-2 mg / mL of the modified solution were mixed, heated and ultrasonicated, and then deionized water was added, centrifuged once, the precipitate was washed, and then dispersed with deionized water, centrifuged twice, the upper liquid was taken, and dried to obtain a modified CeO2 / MoS2 composite nanomaterial; S4. Disperse the modified CeO2 / MoS2 composite nanomaterial obtained in step S3 in deionized water, add a surfactant, ultrasonically disperse, add the modified graphene, ultrasonically disperse, then add a reducing agent, perform a hydrothermal reaction, wash, and dry to obtain an adsorption material.
2. The method for preparing an adsorption material based on molybdenum disulfide according to claim 1, characterized in that: The mass ratio of ammonium molybdate tetrahydrate to thiourea in step S1 is 1:(2-2.2).
3. The method for preparing a molybdenum disulfide-based adsorption material according to claim 1, characterized in that: The mass ratio of nano-molybdenum disulfide and cerium nitrate hexahydrate in step S2 is (2.4-3):
1.
4. The method for preparing a molybdenum disulfide-based adsorption material according to claim 1, characterized in that: The modifying liquid in step S3 is an aqueous solution of 6-amino-1-mercaptohexane hydrochloride.
5. The method for preparing a molybdenum disulfide-based adsorption material according to claim 1, characterized in that: The usage ratio of the CeO2 / MoS2 composite nanomaterial and the modified liquid in step S3 is 1g: (600-800)ml.
6. The method for preparing an adsorption material based on molybdenum disulfide according to claim 1, characterized in that: The parameters of the first centrifugation in step S3 are 10000-15000 rpm for 20-40 min, and the parameters of the second centrifugation are 3500-6000 rpm for 10-20 min.
7. The method for preparing an adsorption material based on molybdenum disulfide according to claim 1, characterized in that: The mass ratio of the modified CeO2 / MoS2 composite nanomaterial and the modified graphene in step S4 is (45-55):
1.
8. The method for preparing an adsorption material based on molybdenum disulfide according to claim 1, characterized in that: The method for preparing the modified graphene in step S4 comprises the following steps: The graphene oxide and deionized water are mixed, ultrasonically dispersed, and then chloroacetic acid and sodium hydroxide are added, ultrasonicated, stirred for 10-16 hours, centrifuged, washed, dried, and ground to obtain modified graphene.
9. The method for preparing a molybdenum disulfide-based adsorption material according to claim 8, characterized in that: The mass ratio of the graphene oxide, chloroacetic acid and sodium hydroxide is 1:(2.2-2.6):(3-3.8).
10. An adsorption material based on molybdenum disulfide obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
An adsorption material, its preparation method and application
CN115554975B
Graphene nano sheet / MoS2 composite nano material and synthesis method thereof
CN102142551A
Hydrothermal preparation method for single-layer MoS2 and graphene composite nano material
CN102698774A
Method for preparing monolayer MoS2 and graphene compounded nano material
CN102701192A
Preparation method and application of three-dimensional cathode material
CN110642333A
Cited By
Irradiation energy-absorbing coating for laser and preparation method thereof
CN120424522A